Synergistic killing of human leukaemic lymphoblasts by glucocorticoids and cytosine arabinoside. - Gledhill, R. M. (Nature Publishing Group, 1983)
Previous work has shown that the lethal effects of glucocorticoids on the human lymphoblastoid cell line, CEM-C7, are antagonized by the simultaneous presence of 1-beta-D-arabinofuranosylcytosine (Ara-C). A possible cell cycle mechanism prompted further studies using flow microfluorimetry. We now report that (1) Ara-C (10-100 nM) blocks cells in S-phase and (2) the block is reversible after the drug is removed. A second treatment protocol, in which glucocorticoid is added to cells recovering from the effects of 24 h exposure to Ara-C, results in a clear synergism between the 2 drugs. This synergism is observed over a range of concentrations (5-100 nM), but is most significant at low doses, where inhibition of cell growth by Ara-C occurs but cell killing is minimal. Prior treatment with Ara-C increases the number of cells killed in the presence of steroid during the period 12-24 h after removal of the S-phase block. Combinations of Ara-C and steroid can thus be either synergistic or antagonistic, depending on the drug scheduling.